2015
DOI: 10.3390/su70912787
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sizing of a Hybrid Grid-Connected Photovoltaic–Wind–Biomass Power System

Abstract: Hybrid renewable energy systems (HRES) are a trendy alternative to enhance the renewable energy deployment worldwide. They effectively take advantage of scalability and flexibility of these energy sources, since combining two or more allows counteracting the weaknesses of a stochastic renewable energy source with the strengths of another or with the predictability of a non-renewable energy source. This work presents an optimization methodology for minimum life cycle cost of a HRES based on solar photovoltaic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 50 publications
(68 reference statements)
0
32
0
Order By: Relevance
“…When the total power output of wind and photovoltaic is greater than the actual demand of the load, the energy storage should be used for regulation Plimit()t+PESS()t=PW()t+PV()t. …”
Section: A Complementary Coordination Dispatch Methods For Integrated mentioning
confidence: 99%
“…When the total power output of wind and photovoltaic is greater than the actual demand of the load, the energy storage should be used for regulation Plimit()t+PESS()t=PW()t+PV()t. …”
Section: A Complementary Coordination Dispatch Methods For Integrated mentioning
confidence: 99%
“…A hybrid system is a combination of one or more resources of renewable energy such as solar, wind, micro/minihydropower and biomass with other technologies such as batteries and diesel generator [8,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The hybrid system studied in this work is one combining solar PV and wind turbine with diesel generator(s) and bank of batteries, which are included for backup purposes.…”
Section: Design Of Hybrid Power Generation Systemmentioning
confidence: 99%
“…Others [6] [7] have developed heuristic methodologies, relying on evolutionary algorithms to optimize micro grids or HRESs size according to cost, environmental, or reliability parameters. However, few of them deal with solar-, wind-, and biomass-resource hybridization in a grid-connected scheme [8] - [11]. In [12] the authors showed that the Moroccan climate is very favorable for the installation of gridconnected microgrid in several regions of the country.…”
Section: Introductionmentioning
confidence: 99%